PERILAKU LATERAL SIKLIK PORTAL BETON BERTULANG BERISI DINDING BATA MERAH - Sari, Mutia Intan; Abdullah, Abdullah; Afifuddin, Mochammad (JURNAL TEKNIK SIPIL, 2018)
Abstract: Generally, brick masonry is used as infill wall material for houses and buildings. The Infill wall is installed once the structure is constructed, and assumed as the dead load for the structure. In fact, infill wall may contribute significant stiffness to the structure. As a consequent, the structure may develop such higher base shear forces due to the large stiffness of the structure. The purpose of this research is to evaluate the behavior of the reinforced concrete frame specimen with red brick infill wall and the specimen without using any infill wall. The size of the frame specimen is 2350 x 3300 mm, which consists of reinforced concrete bare frame specimen and reinforced concrete frame specimen with brick masonry infill wall. Cyclic loading tests were conducted on the specimens on the top beam of frame by in-plane direction. The displacement loading protocol are performed laterally and determined by the measured maximum of LVDT from the beam-column connection. Based on the experimental result, the increase capacity and the obtained energy dissipation of the infill wall frame specimen is up to 11.65 and 3.54 higher respectively, compared to the bare frame specimen. The decrease of the stiffness and the ductility level of the infill wall specimen is lesser in comparison with the bare frame specimen. The typical failure mechanism of the infill wall specimens is diagonal cracking.Abstrak: Material bahan bangunan pengisi dinding untuk pembangunan rumah tinggal dan gedung umumnya menggunakan bata merah. Dinding pengisi dipasang apabila struktur utama selesai dikerjakan dan dianggap sebagai beban mati. Namun pada kenyataannya struktur bangunan yang memiliki dinding mempunyai kekakuan struktur yang besar. Ditinjau dari aspek kegempaan, struktur bangunan dengan kekakuan yang besar maka semakin besar pula beban gempa yang bekerja. Tujuan dari penelitian ini menganalisis perilaku portal beton bertulang dengan dinding bata merah yang dibandingkan dengan portal beton bertulang tanpa dinding. Pengujian yang dilakukan adalah portal beton bertulang dengan ukuran 2350 3300 mm berjumlah 2 sampel yaitu: portal tanpa dinding dan portal berdinding bata merah dengan plasteran. Pengujian portal dilakukan dengan beban lateral siklik dengan arah pembebanan sejajar bidang balok (in plane) pada balok bagian atas portal. Mekanisme pembebanan dilakukan dengan kontrol beban yang ditentukan oleh perpindahan maksimum yang terukur dari LVDT dari join kolom-balok. Hasil penelitian ini menunjukkan terjadinya peningkatan kapasitas dan energi disipasi sebesar 11,65 kali dan 3,54 kali dari portal tanpa dinding. Penurunan kekakuan dan daktilitas yang terjadi lebih kecil dari portal tanpa dinding. Pola kehancuran yang terjadi pada portal berisi dinding bata merah yaitu jenis diagonal cracking